Iterative Algorithm for extended mixed equilibrium problem - Ahmad, Rais; Rizvi, Haider Abbas; Kilicman, Adem (BİSKA Bilisim Company, Yildiz Technical University, Teknopark, 2016)
In this paper, we introduce and study an extended mixed equilibrium problem by using auxiliary principle technique. A generalized predictor-corrector iterative algorithm is deﬁned for solving extended mixed equilibrium problem. The convergence of the method mentioned requires some condition (∗), g-relatively relaxed Lipschitz continuity and relatively g-relaxed monotonicity of the mappings.